The influence of achievement motivation on college students’ employability: A chain mediation analysis of self-efficacy and academic performance - Li, Xiang; Pu, Ruihui; Phakdeephirot, Nutteera (Frontiers in Psychology, 2022)
Employability of college students has been attached great importance by higher education institutions, employers and governments because college graduates are the strategic human resource for the sustainable growth of universities, organizations and countries across the world. It is also receiving growing attention from academic community. This study aimed to examine the psychological mechanism that impacts college students’ employability. It adopted an empirical approach by collecting data from 646 final-year students from 9 universities in the mainland of China. SPSS 25.0 was used for description, correlation and regression analysis. AMOS 24.0 was utilized for path analysis. Model 6 Bootstrap method of PROCESS Version 3.5 was adopted for mediation analysis. The results showed that achievement motivation positively predicted self-efficacy, academic performance and employability among undergraduates. Participants’ self-efficacy did not significantly impact their employability and play a mediating role in the relationship between achievement motivation and employability, while academic performance was a significant mediator of this association. Self-efficacy and academic performance served as chain mediators in the prediction of achievement motivation on college students’ employability. After controlling gender and family residence, achievement motivation still had significant and positive impact on employability of college students. This research made several noteworthy contributions to the existing studies on college students’ employability and provided insight for practitioners in strengthening their employability through these psychological constructs.